1999
DOI: 10.1093/hmg/8.13.2533
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of SURF-1 Expression and Surf-1p Function in Normal and Disease Conditions

Abstract: Loss-of-function mutations of the SURF-1 gene have been associated with Leigh syndrome with cytochrome c oxidase (COX) deficiency. Mature Surf-1 protein (Surf-1p) is a 30 kDa hydrophobic polypeptide whose function is still unknown. Using antibodies against a recombinant, hemagglutinin-tagged Surf-1p, we have demonstrated that this protein is imported into mitochondria as a larger precursor, which is then processed into the mature product by cleaving off an N-terminal leader polypeptide of approximately 40 amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
93
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 22 publications
7
93
0
Order By: Relevance
“…They have concluded that different mutations spanning the first 770 nucleotides of SURF1 lead to the absence of transcript. These results suggested that alterations in the initial region of the gene are probably associated with severe mRNA instability (Tiranti et al, 1999), which might be also occurring with the identified deletion SURF1 transcripts of the present work.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…They have concluded that different mutations spanning the first 770 nucleotides of SURF1 lead to the absence of transcript. These results suggested that alterations in the initial region of the gene are probably associated with severe mRNA instability (Tiranti et al, 1999), which might be also occurring with the identified deletion SURF1 transcripts of the present work.…”
Section: Discussionsupporting
confidence: 68%
“…This duplication is predicted to generate a stop codon in amino acid 291 (p.Lys291X), resulting in a protein possibly smaller in 9 amino acids compared to the normal Surf1p. According to Tiranti et al (1999), this alteration generates a truncated protein with residual complex IV activity (Tiranti et al, 1999). The reported deficiency may be due to a loss of Surf1p conserved C-terminus transmembrane domain integrity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surf1 is ubiquitously expressed in human tissues, in particular in aerobic tissues such as heart, skeletal muscle, and kidney (Yao and Shoubridge 1999). The protein (SURF1), which is highly conserved from recent prokaryotes to humans (Poyau et al 1999), is characterized by an N-terminal mitochondrial targeting sequence and by two transmembrane domains and it is actively imported into mitochondria where it localizes to the inner membrane (Tiranti et al 1999a;Yao and Shoubridge 1999). More than 50 mutations of human 1 These authors contributed equally to this work.…”
mentioning
confidence: 99%
“…COX is the terminal enzyme in both the eukaryotic and prokaryotic respiratory chain, catalyzing the reduction of molecular oxygen to water with concomitant proton pumping from the matrix to the intermembrane space. Studies in Surf1ÿ/ÿ cells from humans (Tiranti et al 1999a), mice (Agostino et al 2003), and yeast (Nijtmans et al 2001) indicate that SURF1 is involved in COX assembly. However, in human Surf1ÿ/ÿ cells low amounts of apparently fully assembled COX can still be detected by 2D-blue native electrophoresis, suggesting redundancy of the SURF1 function via unknown mechanism(s) (Coenen et al 1999;Tiranti et al 1999a;Hanson et al 2001).…”
mentioning
confidence: 99%